Genetic Ablation of the Inducible Form of Nitric Oxide in Male Mice Disrupts Immature Neuron Survival in the Adult Dentate Gyrus - Gabriel G. Fernandes (Frontiers Media S.A., 2021)
Inducible nitric oxide synthase (iNOS) is an enzyme upregulated in the brain during neuroimmune stimuli which is associated with an oxidative and pro-inflammatory environment in several brain regions, including the hippocampal formation and the prefrontal cortex. The dentate gyrus of the hippocampal formation is the site of a process known as adult hippocampal neurogenesis (AHN). Although many endogenous and extrinsic factors can modulate AHN, the exact participation of specific proinflammatory mediators such as iNOS in these processes remains to be fully elucidated. Here, we investigated how the total genetic ablation of iNOS impacts the hippocampal neurogenic niche and microglial phenotype and if these changes are correlated to the behavioral alterations observed in iNOS knockout (K.O.) mice submitted or not to the chronic unpredictable stress model (CUS - 21 days protocol). Contrary to our initial hypothesis, at control conditions, iNOS K.O. mice displayed no abnormalities on microglial activation in the dentate gyrus. However, they did exhibit impaired newborn cells and immature neuron survival, which was not affected by CUS. The reduction of AHN in iNOS K.O. mice was accompanied by an increased positive coping response in the tail suspension test and facilitation of anxiety-like behaviors in the novelty suppressed feeding. Next, we investigated whether a pro-neurogenic stimulus would rescue the neurogenic capacity of iNOS K.O. mice by administering in control and CUS groups the antidepressant escitalopram (ESC). The chronic treatment with ESC could not rescue the neurogenic capacity or the behavioral changes observed in iNOS K.O. mice. Besides, in the ventromedial prefrontal (vmPFC) cortex there was no change in the expression or the chronic activation of PV neurons (evaluated by double labeling PV with FOSB) in the prelimbic (PrL) or infralimbic subregions. FOSB expression, however, increased in the PrL of iNOS K.O. mice. Our results suggest that iNOS seems essential for the survival of newborn cells and immature neurons in the hippocampus and seem to partially explain the anxiogenic-like behavior observed in iNOS K.O. mice. On the other hand, the iNOS ablation appears to result in increased activity of the PrL which could explain the antidepressant-like behaviors of iNOS K.O mice.